Nordic Economic Policy Review - Roine, Jesper (TemaNord, 2016)
The Nordic Economic Policy Review is published by the Nordic Council of Ministers. This year's issue is part of the Danish presidency programme for the Nordic Council of Ministers in 2015. The review addresses policy issues in a way that is useful for in-formed non-specialists as well as for professional economists. All articles are commissioned from leading professional economists and are subject to peer review prior to publication. The review appears once a year. It is published electronically on the website of the Nordic Council of Ministers: www.norden.org/en. On that website, you can also order paper copies of the Review (enter the name of the Review in the search field, and you will find all the information you need).